I “…I Felt More Challenged to Keep Practicing”: An Exploration of the Students’ Voice towards Elsa Speak for Supplementing Students’ Speaking Willingness - Khadijah, Asnah Nurul; Rosyidah, Linda Imamatul; Elfiyanto, Sony (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This study aims at discovering out the students’ perceptions about using Elsa Speak in learning English. Sources of data for this study were 15 junior high school students. In collecting data, the researcher spread the questionnaires by using Google Forms format and the researcher used an interview to support the questionnaire result towards the students’ voice in utilizing Elsa Speak. Statistical analysis was performed using SPSS software. The results show that students have a fairly positive perception towards the use of Elsa Speak in learning English. It indicates that students like the use of Elsa Speak in learning process, they can read the words, phrases, and situational sentence patterns themselves and then be assessed and corrected by ELSA's artificial intelligence, they can find out how much they can pronounce sentences according to native standards. Students also get many advantages with Elsa Speak.